KINERJA DAN PERSPEKTIF PENGEMBANGAN MODEL AGROPOLITAN DALAM MENDUKUNG PENGEMBANGAN EKONOMI WILAYAH BERBASIS AGRIBISNIS - I WAYAN RUSASTRA; HENDIARTO -; KHAIRINA M. NOEKMAN; ADE SUPRIATNA; WAHYUNING K. SEJATI; DERI HIDAYAT (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2005)
The implementation of agropolytant have strong justification and considered to be abreakthrough program to strengthen the achievement of agribusiness development for the benefit ofthe farmers as well as regional economic development. The study consists of two main activities, i.e.:(a) To evaluate the concept and the achievement of agropolytant program; and (b) To assess the ongoingagropolytant pilot project. The strengthening of agropolytant development has to be facilitatedwith suitable strategic policies of domestic price stability, better accessibility to input market andprocessing, better urban functionality, and accelerated rural-urban flow for the benefit of rural people.In addition, the policy of agropolytant program credit scheme (BLM) have to be complemented andfacilitated with strong self-help farmer group and cooperative marketing institutional development.Agropolytant development has been able to improve farmer income, but absolutely the farmer incomeis still low, due to restricted resource endowment. Agropolytant program working group (Pokja) atregency level has well functionality, and Agropolytant Regional Management Agency (BPKAP) atprovincial and regency level are badly needed. The existence of BPKAP will have important role insupporting the efectivity, performance, and accountability of agropolytant program. Governmentsupport have been implemented well. The achievement of those facilities have to be complementedwith proper incentive system for all parties participated in agropolytant development program.